EFFECT OF DRYING AND FRYING ON QUALITY OF LIANG VEGETABLE - Klompong, Vilailak; Bupphakit, Naruemon; Chumdang, Siriyakorn (LIFE: International Journal of Health and Life-Sciences, 2020)
Liang vegetable (Gnetumgnemon) is originated in the Malay Peninsula and become the local southern vegetable of Thailand. Liang vegetables possess high nutritional value and bioactive compounds associated with antioxidant effects. This research aims to develop crispy Liang vegetable products as a functional snack food with antioxidant activity by studying drying and frying conditions suitable for the product and also analyzing the quality of the finished product. After study on the effect of maturity of leaves on the rank smell by categorizing Liang vegetables into 3 types by color, including old leaves (L* = 110.26, a* = -10.90, b* = 27.66), medium leaves (L* = 115.26, a* = -5.93, b* = 36.33). Young leaves (L* = 115.36, a* = 3.36, b* = 35.10), the result showed that the medium leaves got the highest score of smell preference, followed by old leaves and young leaves (p<0.05) respectively. Thereafter, a study on the effect of drying temperature on sensory quality was conducted. The result exhibited that at 70 ºC the product obtained got the highest hedonic scores in terms of texture, color, smell, and overall liking (p<0.05). In addition, the frying temperature at 60ºC was appropriated for producing crispy Liang vegetables, when the sensory evaluation including texture, color, smell, crispness, and overall liking was tested (p<0.05). The hardness of the finished product was 301.79 g when measuring with a texture analyzer. Aw and yeasts and mold of the finished product were 0.47 and 2.2 cfu/g, respectively. The crispy Liang vegetable product also possessed antioxidant activity (DPPH radical scavenging activity, 55.06%). Therefore, the quality of crispy Liang vegetable was designated by drying and frying conditions. Additionally, the crispy Liang vegetable possessed antioxidant activity and conformed to the safety of Thailand community product standards. Thus, crispy Liang vegetable products could be served as functional vegetable-based snacks with antioxidant activity for consumer compliance.